Snailology - Ross, Michael Elsohn, 1952-; Grogan, Brian, 1951-; Erickson, Darren (Minneapolis, MN : Carolrhoda Books, 1996)
Provides instructions for finding, collecting, and keeping snails and suggests how to delve into the secret lives of these shell dwellers.
Includes index.
School Library Journal.
The Science Teacher (N.S.T.A.).
5.5
3-6
Keywords: Snails -- Juvenile literature; Snails -- Experiments -- Juvenile literature; Snails as pets -- Juvenile literature; Snails; Snails; Snails -- Experiments; Science -- Experiments; Snails; Snails as pets